Exploring the Nexus Between Health Literacy and Understanding of Processed Foods in Consumers. - Özdemir, Aslıhan; Yetişen, Lütfiye Parlak; Karael, Buse; Kotzaoglan, Raife; Dikmen, Derya (Hacettepe University Faculty of Health Sciences Journal)
Objective: The research explores how health literacy (HL) relates to understanding about processed foods among consumers. Materials and Methods: A questionnaire was employed to collect data and opinions from 1246 healthy adults with bachelor's degrees on minimally and ultra-processed foods. To classify the food items, the NOVA system was employed, and HL was evaluated using the Newest Vital Sign questionnaire. Results: Adequate HL was identified in 48.8% of participants. Women demonstrated significantly higher HL scores than men (p<0.001), and a significant negative correlation was observed between age and HL (r = -0.115, p<0.001). Regarding knowledge of food processing, 73.7% of participants reported awareness of the terms "minimal" and "ultra-processed," although only 46.1% indicated familiarity with their meanings. Notably, 73.7% of subjects incorrectly classified standard food preparation methods such as boiling, freezing, and frying as indicators of ultra-processed foods. Across most knowledge items, the proportion of correct and incorrect responses did not vary significantly by HL level. However, participants with limited HL were more likely to disapprove of processed and ultra-processed foods. In contrast, those with adequate literacy were more likely to acknowledge potential health benefits of food processing and less likely to overgeneralize by categorizing all industrial foods as ultra-processed (p<0.001). Conclusions: Despite adequate HL in half the participants, the public's unfamiliarity with food processing levels may negatively impact health decisions. Enhancing consumer understanding requires emphasizing food literacy skills, necessitating additional educational interventions beyond HL.